The use of hypotonic fluids in paediatric practice. (4th April 2011) - Baker, J; Armon, K; Playfor, S; Rackham, O
Abstract : Background: The use of hypotonic intravenous fluids in children has been associated with significant electrolytes abnormalities. In particular, 0.18% sodium chloride with 4% glucose has been linked with hyponatraemia, even death. In 2004, Armon et al 1 conducted an audit describing the types of fluid prescribed in paediatric wards. This concluded that most children received hypotonic fluids, electrolyte abnormalities were common and that few units (30%) had guidelines for prescribing intravenous fluids. In 2007 the National Patient Safety Agency (NPSA) published advice on administering intravenous fluids in children. This recommended removing 0.18% sodium chloride with 4% glucose from 'general' ward areas. Aims: To describe ▶ the types of fluids used in paediatric wards following the NPSA alert, ▶ the frequency of electrolyte disturbance, ▶ the number of units with guidelines for prescribing fluids. Method: A prospective multicentre 'snapshot' audit. Centres that had participated in the original audit and all members of the Paediatric Research Society were invited to participate. Data were collected using a standard proforma. All patients on paediatric wards (excluding neonatal units) were eligible. Results: Results were received from 36 hospitals, for 234 patients. Most (60%) were 'general paediatric' patients, while 32% were under surgical care. The commonest reasons for intravenous fluid administration were 'nil by mouth' (39%), decreased intake (30%) and rehydration (17%). Hypotonic fluids were given to 116 children (of which 93 received 0.45% sodium chloride with 5% glucose). Isotonic fluids were prescribed for 112 children. No patients received 0.18% sodium chloride with 4%glucose. 30 patients had not had electrolytes checked since starting intravenous fluids. Hyponatraemia was found in 20 patients, 12 of which received hypotonic fluids. Hypernatraemia was found in 13 patients, 8 of which received hypotonic fluids. Of the 36 hospitals, 28 had guidelines for prescribing intravenous fluids. Conclusion: In a 'snapshot' survey of 36 hospitals across the UK, paediatric patients are no longer receiving 0.18% sodium chloride with 4% glucose, in line with the NPSA alert. However, half of the patients received hypotonic fluids; most commonly 0.45% sodium chloride with 5% glucose. More units have guidelines for prescribing intravenous fluids, but in a quarter of units junior doctors still prescribe intravenous fluids without clear guidelines.